2012
DOI: 10.1186/1471-2202-13-75
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture regulates the glucose metabolism in cerebral functional regions in chronic stage ischemic stroke patients—a PET-CT cerebral functional imaging study

Abstract: BackgroundAcupuncture has been applied to aid in the recovery of post-stroke patients, but its mechanism is unclear. This study aims to analyze the relationship between acupuncture and glucose metabolism in cerebral functional regions in post-stroke patients using 18 FDG PET-CT techniques. Forty-three ischemic stroke patients were randomly divided into 5 groups: the Waiguan (TE5) needling group, the TE5 sham needling group, the sham point needling group, the sham point sham needling group and the non-needling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
(29 reference statements)
1
30
0
Order By: Relevance
“…A number of clinical studies and evidence-based literature analyses have demonstrated that acupuncture has a positive effect on post-stroke rehabilitation (Huang et al, 2012). However, the underlying mechanisms are still unclear.…”
Section: Management and Treatmentmentioning
confidence: 99%
“…A number of clinical studies and evidence-based literature analyses have demonstrated that acupuncture has a positive effect on post-stroke rehabilitation (Huang et al, 2012). However, the underlying mechanisms are still unclear.…”
Section: Management and Treatmentmentioning
confidence: 99%
“…Most of the studies were conducted in China (80 studies) [10, 11, 13, 14, 16, 1824, 26, 27, 2931, 3336, 4346, 48, 51, 53, 54, 56, 5866, 6870, 7275, 77, 78, 83, 84, 86, 87, 89, 90, 93, 95, 97, 99101, 104, 111, 113, 115, 123, 137, 138, 142, 144147, 154, 159, 161166] and in USA (40 studies) [15, 28, 37, 38, 42, 57, 70, 71, 76, 80, 88, 91, 94, 96, 105107, 118120, 124127, 129131, 133136, 140, 141, 148, 151, 152, 155, 156, 158, 174]. The investigators in Korea (16 studies) [7, 47, 49, 52, 55, 82, 85, 98, 102, …”
Section: Resultsmentioning
confidence: 99%
“…25 studies were [10, 2629, 34, 38, 49, 51, 5860, 62, 65, 71, 84, 101, 105, 108, 112, 134, 137, 139, 142, 145] performed on patients. 21 studies [14, 1823, 37, 40, 4648, 52, 61, 77, 131, 133, 138, 141, 146, 165] recruited both healthy subjects and patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations